Stochastic Motion Stimuli Influence Perceptual Choices in Human Participants - Fard, Pouyan R.; Bitzer, Sebastian; Pannasch, Sebastian; Kiebel, Stefan J. (Frontiers in Neuroscience, 2022)
In the study of perceptual decision making, it has been widely assumed that random fluctuations of motion stimuli are irrelevant for a participant’s choice. Recently, evidence was presented that these random fluctuations have a measurable effect on the relationship between neuronal and behavioural variability, the so-called choice probability. Here, we test, in a behavioural experiment, whether stochastic motion stimuli influence the choices of human participants. Our results show that for specific stochastic motion stimuli, participants indeed make biased choices, where the bias is consistent over participants. Using a computational model, we show that this consistent choice bias is caused by subtle motion information contained in the motion noise. We discuss the implications of this finding for future studies of perceptual decision making. Specifically, we suggest that future experiments should be complemented with a stimulus-informed modeling approach to control for the effects of apparent decision evidence in random stimuli.